EVALUASI ANTARMUKA PERMAINAN 3D BALAP KARUNG MENGGUNAKAN METODE SYSTEM USABILITY SCALE (SUS) - Adi Sucipto; Anugrah Dwirangga; RM. Joko Priyono (J-ICON : Jurnal Komputer dan Informatika, 2023)
Traditional games are a form of knowledge passed down from generation to generation. An example of a traditional game is Balap Karung. Currently, many game developers have created the "Balap Karung" application, but it has deficiencies in its User Interface. The User Interface is one of the visual elements that build a game. The User Interface is a communication mechanism between the user and the system that can receive information and provide information to the user to help direct the navigation flow until the user finds the solution. Creating a user interface in the 3D" Balap Karung" game as a visual design for the "Balap Karung" game will be built on an Android-based system. Creating a graphic user interface is done by researching the use of color in the user interface. The colors that match the "Balap Karung" game style will be used. The System Usability Scale (SUS) method was used as a usability test for the "Balap Karung" game. Through the results of game testing using the SUS method by distributing online questionnaires to be filled out by the respondents after they played the "Balap Karung" game, was obtained the average SUS score of 69.42 after calculating the results of the questionnaires from the respondents. According to the scores, it can conclude that the usability of the "Balap Karung" game is said to be good, with buttons and visuals following the purpose of their respective functions. According to the theory of calculating the SUS score, a score of 69.42, the "Balap Karung" game gets a Good rating in terms of usability.